High‐resolution imaging of fluorescent whole mouse brains using stabilised organic media (sDISCO). Issue 8 (29th April 2019) - Hahn, Christian; Becker, Klaus; Saghafi, Saiedeh; Pende, Marko; Avdibašić, Alma; Foroughipour, Massih; Heinz, Daniel E.; Wotjak, Carsten T.; Dodt, Hans‐Ulrich
Abstract : Optical tissue clearing using dibenzyl ether (DBE) or BABB (1 part benzyl alcohol and 2 parts benzyl benzoate) is easy in application and allows deep‐tissue imaging of a wide range of specimens. However, in both substances, optical clearing and storage times of enhanced green fluorescent protein (EGFP)‐expressing specimens are limited due to the continuous formation of peroxides and aldehydes, which severely quench fluorescence. Stabilisation of purified DBE or BABB by addition of the antioxidant propyl gallate efficiently preserves fluorescence signals in EGFP‐expressing samples for more than a year. This enables longer clearing times and improved tissue transparency with higher fluorescence signal intensity. The here introduced clearing protocol termed stabilised DISCO allows to image spines in a whole mouse brain and to detect faint changes in the activity‐dependent expression pattern of tdTomato. Abstract : Stabilisation of organic media as dibenzyl ether by the addition of the antioxidant propyl gallate efficiently preserves fluorescence signals in EGFP‐expressing samples during optical tissue clearing and storage for more than a year. This enables longer clearing times and improved tissue transparency with higher fluorescence signal intensity. This clearing protocol termed sDISCO allows to image spines in a whole mouse brain and to detect faint changes in activity‐dependent expression patterns.